'Scalp coordinate system': a new tool to accurately describe cutaneous lesions on the scalp: a pilot study. Issue 4 (12th June 2018) - Alexander, William; Miller, George; Alexander, Preeya; Henderson, Michael A.; Webb, Angela
Abstract : Background: Skin cancers are extremely common and the incidence increases with age. Care for patients with multiple or complicated skin cancers often require multidisciplinary input involving a general practitioner, dermatologist, plastic surgeon and/or radiation oncologist. Timely, efficient care of these patients relies on precise and effective communication between all parties. Until now, descriptions regarding the location of lesions on the scalp have been inaccurate, which can lead to error with the incorrect lesion being excised or biopsied. Methods: A novel technique for accurately and efficiently describing the location of lesions on the scalp, using a coordinate system, is described (the 'scalp coordinate system' (SCS)). This method was tested in a pilot study by clinicians typically involved in the care of patients with cutaneous malignancies. A mannequin scalp was used in the study. Results: The SCS significantly improved the accuracy in the ability to both describe and locate lesions on the scalp. This improved accuracy comes at a minor time cost. Discussion: The direct and indirect costs arising from poor communication between medical subspecialties (particularly relevant in surgical procedures) are immense. An effective tool used by all involved clinicians is long overdue particularly in patients with scalps with extensive actinic damage, scarring or innocuous biopsy sites. The SCS provides the opportunity to improve outcomes for both the patient and healthcare system.